1297 A Randomized Clinical Trial of the Use of Oral Glucose for Pain Relief During Retinopathy of Prematurity Examination (ROP). (October 2012) - Procianoy, RS; Costa, M; Eckert, G; Fortes, B Borges; Filho, J Fortes; Silveira, RC
Abstract : Background: Ophthalmologic examination for ROP is a painful procedure. Pharmacological and non-pharmacological interventions have been proposed in order to reduce pain during eye examination. Purpose: To evaluate the use of oral 25% glucose solution to relief pain during ophthalmologic examinations for ROP. Methods: A masked randomized clinical trial with the use of 1 ml of oral 25% glucose solution once 2 minutes before the first ophthalmologic examination was carried out from March 2008 to April 2010 comparing with a control group that did not receive oral glucose solution. Pain was evaluated by Neonatal Infant Pain Scale (NIPS) immediately before and immediately after the ophthalmologic examination in both groups. Results: 124 patients who were examined for the first time for ROP were included (70 in intervention and 54 in control groups). Prior to examination, mean NIPS scores were 0.8±0.8 and 1.2±1.2 (P=0.100) in newborns of intervention and control groups respectively, and after examination mean NIPS scores were 2.6±1.1 and 4.5±1.3 (P<0.001) in intervention and control groups respectively. The number of patients with pain prior the eye examination was one (1.4%) and 2 (3.7%) in intervention and control groups (P=0.580) respectively. After eye examination 11 patients with pain (NIPS≥4) in intervention group (15.7%) and 37 patients with pain (68.5%) in control group (P<0.001). Conclusions: One ml of oral 25% glucose solution given 2 minutes before the ophthalmologic examination for ROP is an effective measure for pain relief. (clinicaltrials.gov. NCT00648687 ).